Increased Preoperative Plasma Level of Microbial 16S rDNA Translocation Is Associated With Relapse After Prostatectomy in Prostate Cancer Patients - Ou, Tongwen; Zhou, Zejun; Turner, David P.; Zhu, Baoli; Lilly, Michael; Jiang, Wei (Frontiers in Oncology, 2020)
The environmental factors for promoting prostate cancer (PCa) progression remain unknown. Methods. A retrospective cross-sectional study was conducted in healthy men (n = 12) and PCa patients undergoing prostatectomy (n = 27). Plasma preoperative level of total cell-free bacterial 16S rDNA, a marker of microbial translocation, was evaluated by qPCR. Plasma levels of prostate-specific antigen (PSA) were evaluated by ELISA. Results. Similar degrees of microbial translocation were found in healthy men and patients. However, the levels of microbial 16S rDNA were increased in patients with cancer relapse (n = 10) compared to patients without relapse (n = 17) after prostatectomy. Furthermore, the levels of microbial 16S rDNA were marginally increased in patients with pT3 or pT4 tumors compared to those with pT 2 or less. The levels of microbial 16S rDNA tended to increase in patients with higher pathologic tumor stage, Gleason score, and marginal and lymph node involvements; but these differences did not reach significance. Conclusion. Systemic microbial translocation may play a role in PCa progression. Measurement of plasma total bacterial rDNA levels may be used as a non-invasive method to predict PCa relapse after prostatectomy.